An Annotated Translation of Canvas - Carmelia Avelyne Nancy Lay; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
In this study, the writers discussed difficulties, solutions, and strategies used to translate poems of Canvas by doing an annotated translation. The data was taken from the book entitled ‘Canvas’ by Beni Wego. The strategies that the writers used were four strategies by Lefevere (1975), eight strategies by Baker (2018) and two strategies by Newmark (1988). Then, there were two most suitable strategies used which were translation by paraphrase using a related word and free translation. From the analysis, the difficulties were dealing with words that have similar meaning, difficult words to be translated in the TL, length of words, literal meaning, non-equivalent words, words that have multiple meanings, words that cannot be lexicalized, unimportant words, information, words that need more explanation, and idiom structure. From this study, it could be concluded that doing annotated translation help the process of finding out difficulties and solutions.